Automated epidermal thickness quantification of in vitro human skin equivalents using optical coherence tomography - Martina M Sanchez; Danielle N Orneles; B Hyle Park; Joshua T Morgan (BioTechniques)
Human skin equivalents (HSEs) are in vitro models of human skin. They are used to study skin development, diseases, wound healing and toxicity. The gold standard of analysis is histological sectioning, which both limits three-dimensional assessment of the tissue and prevents live culture monitoring. Optical coherence tomography (OCT) has previously been used to visualize in vivo human skin and in vitro models. OCT is noninvasive and enables real-time volumetric analysis of HSEs. The techniques presented here demonstrate the use of OCT imaging to track HSE epidermal thickness over 8 weeks of culture and improve upon previous processing of OCT images by presenting algorithms that automatically quantify epidermal thickness. Through volumetric automated analysis, HSE morphology can be accurately tracked in real time.